P356 Sudoscan as a diagnostic tool for transthyretin familial amyloid polyneuropathy. Issue 9 (September 2017) - Sousa, Ana; Valdrez, Kátia; Cardoso, Marcio; Anselmo, João; Freitas, Monica; Ferreira, Heder; Coelho, Teresa
Abstract : Objectives: Evaluate the diagnostic utility of Sudoscan for transthyretin familial amyloid polyneuropathy (TTR-FAP). Methods: One hundred and ten TTR-FAP Val50Met carriers were divided in asymptomatic (group 1), with doubtful neurologic symptoms (group 2) and symptomatic stage 1 with less than 3 years of disease (group 3). We analysed quantitative sensory testing with determination of cold detection thresholds (CDT), heart rate variability (HRV), sympathetic skin responses (SSR), sural sensory nerve action potential (SNAP) and electrochemical skin conductance (ESC) measured by Sudoscan in both hands and feet. Statistical analysis was done using SPSS 24.0. Results: Mean age was 35 for group 1, 44 for group 2 and 40 for group 3. Feet and hand ESC were each significantly reduced among symptomatic patients (77 ± 5 vs. 71 ± 12 vs. 53 ± 26 μS p  < 0.0001, and 74 ± 7 vs. 61 ± 16 vs. 55 ± 19 μS p  < 0.0001). Feet ESC correlated significantly with CDT (−0.343, p  < 0.0001), HRV (0.397, p  < 0.0001) and sural SNAP (0.383, p  > 0.0001). ROC analysis for feet and hand ESC showed area under the curve of 0.84 and 0.76, respectively; p  ⩽ 0.0001). Discussion: Except for SSR, all neurophysiological measures were statically different between the 3 groups. Both feet and hand ESC demonstrated strong correlation with CDT, HRV and sural SNAP. ROC curve analysis showed significant results for both hand and feet ESC. Conclusions: These findings suggest that Sudoscan is a promising diagnostic test for TTR-FAP. Significance: Sudoscan should be considered for routine assessment in TTR-FAP Val50Met carriers.